Role of retained austenite with different morphologies on sub-surface fatigue crack initiation in advanced bainitic steels. (15th July 2020) - Gao, Guhui; Liu, Rong; Wang, Kun; Gui, Xiaolu; Misra, R.D.K.; Bai, Bingzhe
Abstract: We describe here the distinct high cycle fatigue properties of advanced bainitic steels to elucidate the significant role of retained austenite with different morphologies on sub-surface fatigue crack initiation process. The inter-plate film-like retained austenite at the straight front of small crack tip transformed to martensite, leading to the arrest of small crack growth and altered the active slip systems. However, the blocky retained austenite or martensite/austenite islands located at prior austenite grain boundaries induced intergranular fatigue cracking because of ease of activation of slip in retained austenite. Graphical abstract: Image, graphical abstract